Arterial stiffness is associated with handgrip strength in relatively healthy Chinese older adults - He, Yan; Niu, Yue; Li, Zhe; Zhang, Ruimin; Chen, Yizhi; Dong, Zheyi; Zheng, Ying; Wang, Qian; Wang, Yong; Zhao, Delong; Sun, Xuefeng; Cai, Guangyan; et al. (Frontiers in Nutrition, 2024)
Background: Increased arterial stiffness and low handgrip strength (HGS) are associated with poor health outcomes and are a severe health risk for older adults.However, there is limited evidence and mixed results on whether there is an association between them. Therefore, this study focused on the association between arterial stiffness and HGS in relatively healthy older adults in Beijing, China.In 2016, 2,217 adult volunteers were recruited in Beijing. Brachial-ankle pulse wave velocity (baPWV) and the ankle-brachial index were measured using an automatic vascular profiling system. Carotid artery intima-media thickness and common carotid artery-internal diameter (CCAID) were evaluated using Doppler ultrasound, and HGS was measured with a dynamometer. Low HGS was determined using the Asian Sarcopenia Working Group 2019 criteria. Multivariate linear and logistic regressions evaluated the relationship between arterial stiffness and HGS. Results: Ultimately, 776 relatively healthy older adults (mean age 69.05 ± 6.46 years) were included. Based on the AWGS2019 criteria, 137 participants were defined as having low HGS. Compared to the normal HGS group, the low HGS group was older and had higher baPWV (p<0.001) but lower CCAID, body mass index (BMI) and hemoglobin (Hb) (p<0.05). The multiple linear regression analysis revealed that baPWV was negatively correlated with HGS (β=-0.173, t=-2.587, p=0.01). Multivariate logistic regression analysis showed that baPWV and CCAID were associated with an increased risk of low HGS (odds ratio (OR) per SD increase: 1.318, p=0.007; OR per SD increase: 0.541, p<0.001).Conclusions: Arterial stiffness and HGS were significantly negatively correlated in relatively healthy Chinese older adults. Low HGS is associated with increased arterial stiffness. Encouraging exercise training to improve HGS, thereby reducing arterial stiffness and the risk of cardiovascular events, may be a simple and effective intervention.